STUDENTS’ ATTITUDE TOWARD “QUIPPER SCHOOL” AS AN ENGLISH ONLINE LEARNING MEDIA AT SMAN 1 ARGAMAKMURBENGKULU UTARA - Lusynta Febrianti; Mulyadi .; Gita Mutiara Hati (Journal of English Education and Teaching, 2018)
This study aimed to find out students’ attitude toward “Quipper School” as an English online learning media. The population of this research was the whole students of SMAN 1 Argamakmur Bengkulu Utara, with the total population of 667 students. The sample of this research was 158 students. It was chosen by using clustered random sampling. The instrument that was used in this research was questionnaire which consists of 27 items and was divided into three aspects, namely cognitive, affective, and behavior aspect. The interview was used to confirm and to support the data from the questionnaire. The result of this research shows that students had positive attitude toward “Quipper School” as an English online learning media, with the mean score for all aspect was 3.76; the mean score for cognitive aspect was 3.85; the mean score for affective aspect was 3.71; and the mean score for behavior aspect was 3.72. It means that students of SMAN 1 Argamakmur Bengkulu Utara generally have a positive attitude toward “Quipper School” as an English online learning media.